IMPLEMENTASI KERJA SAMA INDONESIA DAN AMERIKA SERIKAT DALAM MENANGGULANGI PENCUCIAN UANG DAN PENDANAAN TERORIS PERIODE 2018-2021 - Novito Budiman (2023)
In recent years, there have been terrorist incidents in the form of attacks, shootings and bombings in various areas in Indonesia. One of the reason is the flow of funds in the form of money laundering used to finance terrorist activities. Over the past few years, law enforcement officials in Indonesia have found several cases related to money laundering and terrorist financing. Seeing that these cases still exist, Indonesia needs an international cooperation on tackling the problem of money laundering and terrorist financing. One of the international cooperation that has been carried out by Indonesia is cooperation with the United States. In this study the authors will discuss cooperation between Indonesia and the United States in the field of money laundering and terrorist financing. This cooperation is carried out in the form of exchange of information between institutions regarding entities or individuals suspected of terrorist financing. This study uses a descriptive qualitative research method. The author also uses several journal articles and conducts interviews with relevant agencies to complete the required data. In this research, the authors also use several theories, including Bilateral Cooperation, Terrorism, and Money Laundering. The research results show that cooperation between Indonesia and the United States in the field of money laundering and terrorist financing has been implemented. This can be proven by exchanging information five times during 2018-2021.